Author Correction: Non-local effect of impurity states on the exchange coupling mechanism in magnetic topological insulators - Thiago R. F. Peixoto (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41535-021-00314-9